Cytotoxicity of Thioalkaloid-Enriched Nuphar lutea Extract and Purified 6,6'-Dihydroxythiobinupharidine in Acute Myeloid Leukemia Cells: The Role of Oxidative Stress and Intracellular Calcium - Suchismita Muduli; Avi Golan-Goldhirsh; Jacob Gopas; Michael Danilenko (MDPI AG, 2022)
Acute myeloid leukemia (AML) is an aggressive hematological malignancy characterized by uncontrolled proliferation of immature myeloid progenitors. Here, we report the in vitro antileukemic effects of the sesquiterpene thioalkaloid-enriched fraction of the Nuphar lutea leaf extract (NUP) and a purified thioalkaloid 6,6'-dihydroxythiobinupharidine (DTBN). Treatment with 0.3-10 µg/mL NUP caused a dose- and time-dependent reduction in proliferation and viability of human AML cells (KG-1a, HL60 and U937). This was associated with apoptosis induction manifested by annexin-V/propidium iodide binding as well as cleavage of caspases 8, 9, and 3 as well as poly (ADP-ribose) polymerase. Caspase-dependence of the apoptotic effect was confirmed using the pan-caspase inhibitor Q-VD-OPH. NUP induced significant biphasic changes in the cytosolic levels of reactive oxygen species (ROS) compared to untreated cells-a decrease at early time points (2-4 h) and an increase after a longer incubation (24 h). ROS accumulation was accompanied by lowering the cellular glutathione (GSH) levels. In addition, NUP treatment resulted in elevation of the cytosolic Ca2+ (Ca2+cyt) levels. The thiol antioxidant and glutathione precursor N-acetyl cysteine prevented NUP-induced ROS accumulation and markedly inhibited apoptosis. A similar antiapoptotic effect was obtained by Ca2+cyt chelating using BAPTA. These data indicate that NUP-induced cell death is mediated, at least in part, by the induction of oxidative stress and Ca2+cyt accumulation. However, a substantial apoptotic activity of pure DTBN (0.05-0.25 µg/mL), was found to be independent of cytosolic ROS or Ca2+, suggesting that alternative mechanisms are involved in DTBN-induced cytotoxicity. Notably, neither NUP nor DTBN treatment significantly induced cell death of normal human peripheral blood mononuclear cells. Our results provide the basis for further investigation of the antileukemic potential of NUP and its active constituents.